Quan hệ Nhật Việt từ sau năm 1954 đến 1975 - Sử, Phạm Quốc (VNU Journal of Science: Social Sciences and Humanities; Vol 20 No 1, 2004)
The relationship of Vietnam and Japan in the period of from 1954 to 1975 is really complicated. This is not only because of its relations with regimes politically opposite in the North and the South, but also because of its relation between Japan and South Vietnam which was patronized by America. However, stalemates in the American strategies as well as the signs of unstableness of the regime of Saigon made Japan cautious of investing into the Southern Vietnam. There is a fact th a t what behind a Japan which has been considered a "tail" of America is still a Japan with the ambition of “Great Common Prosperous East Asia rose" up by Jap an itself. So, Japanese people were not much pro-occupied about “an t i communism” and joined hands with me two regimes: Communism it the North and "the anti-Communist" of the South of Vietnam.